2017
DOI: 10.1021/jacs.7b08642
|View full text |Cite
|
Sign up to set email alerts
|

Control of Fullerene Crystallization from 2D to 3D through Combined Solvent and Template Effects

Abstract: Achieving precise control of molecular self-assembly to form designed three-dimensional (3D) structures is a major goal in nanoscale science and technology. Using scanning tunnelling microscopy and density functional theory calculations, we show that a 2D covalent organic framework (COF-1) can template solution-processed C guest molecules to form several solvent-dependent structural arrangements and morphologies via a 2D to 3D growth process. When 1,2,4-tricholorobenzene is used as solvent, C molecules form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 83 publications
3
45
0
Order By: Relevance
“…Figure a shows an image where a small defect region was identified in a lattice of C 70 /COF‐1. This allows us to use geometric considerations to identify this lattice as a parallel‐shifted R‐layer (Figure c) . A similar shift geometry was observed for C 60 and explained by a template‐induced solvent co‐adsorption effect within the T‐layer.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Figure a shows an image where a small defect region was identified in a lattice of C 70 /COF‐1. This allows us to use geometric considerations to identify this lattice as a parallel‐shifted R‐layer (Figure c) . A similar shift geometry was observed for C 60 and explained by a template‐induced solvent co‐adsorption effect within the T‐layer.…”
Section: Resultssupporting
confidence: 55%
“…In previous work, we have shown that the R1 layer C 60 molecule can shift with respect to the given T‐layer C 60 , which exists in threefold symmetry, forming a less‐dense molecular packing. The shifted positions were found to be stable states explained by a template‐induced solvent coadsorption effect . The same argument can also be applied for C 70 , where the co‐adsorbed solvent molecules are correspondingly observed (Figure S5, Supporting Information).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations